Barriers and breakthroughs: engaging in socially just ways towards issues of indigeneity, identity, and whiteness in teacher education. Issue 1 (2nd January 2019) - Riley, Tasha; Monk, Sue; VanIssum, Harry
ABSTRACT: Within Australia, The Australian Professional Standard for Teachers' Standard 1.4 dictates that teachers should have an understanding and awareness of the histories, cultures and languages of Aboriginal and Torres Strait Islander peoples. Yet non-Indigenous teachers seem reluctant to integrate Indigenous perspectives in the classroom. This study examines how 142 pre-service teachers' views on a first year Indigenous Education course founded upon a social justice/antiracist framework evolved throughout their first term. The article focuses upon specific aspects of the course that pre-service teachers identified as enabling them to move beyond resistance and towards understanding and confidence in relation to their ability to teach issues related to Indigeneity, whiteness, and identity in their own classrooms. Based on pre-service teacher responses, we provide considerations for the development of future courses addressing Indigeneity in relation to design, implementation and collaboration.